Media and interpersonal persuasions in the polio eradication campaign in northern Nigeria - Yakubu Ozohu-Suleimain (Journal of Public Health in Africa, 2010)
This study is premised on the increasing global concerns over the widespread resistance to polio eradication campaign in northern Nigeria. It aims to determine the level of campaign acceptance and compare the influences of mass media and interpersonal communication sources in Zaria local government area, being one of the high-risk (WPV-endemic) areas in northern Nigeria, where campaign resistance is known to be high. By way of quantitative survey, the study utilized 10% sample of the populations of eight out of the thirteen Wards in Zaria local government area, with a response rate of 78.6%. Findings reveal close ranks between campaign acceptance and resistance in the local government area, thus further confirming the difficulties still faced in polio eradication campaign in the region. This study also indicates higher performance of Interpersonal than Mass Media sources in influencing campaign acceptance and resistance in the local communities. Contact with friends and relations was rated the most influential interpersonal sources in the acceptance and resistance decision of individuals, while newspapers and magazines were rated most influential media sources that influenced campaign resistance in the local communities. The study concludes that a polio eradication campaign, backed with competent and sufficient communication expertise that utilizes knowledge-based indigenous interpersonal communication strategies will likely result in greater community acceptance in northern Nigeria.